Customers’ Trust on E-Banking System in Bangladesh - Mohammad Shamsus; Nasrin Mukta; Abdul Hanna (Multidisciplinary Journal of Akseprin Indonesia, 2023)
E-banking is the newest improvement in banking sector which is a latest dimension to banking dealings by permitting customers to perform financial transaction through the delivery channel. The study was designed to investigate practices, impact, security, problems and prospects of e-banking in Bangladesh which are directly related with the trust on electronic banking. To collect data for this study a set of questionnaire was developed with 44 questions which covered the above mentioned elements of e-banking in Bangladesh. Total 224 respondents are selected purposively from bankers and customers of whom 75 bankers and 149 are bank customers of sixteen randomly selected banks. Banks are classified into four categories like state owned commercial bank, domestic private commercial bank, foreign commercial bank and other specialized bank which activates in Bangladesh. Statistical software SPSS was used to analyze data. The result shows that customers trust depends basically on security measures, customers awareness, educational qualification, authentication of etransaction, e-service quality of banks, bankers behavior etc. Every step in the online banking activities is secured by one or more security mechanisms. Customer’s awareness is one of the most important elements to build up trust on e-banking. Low educated people are afraid of doing e-banking operation. Problems or difficulties are directly related with customers trust. If customers trust is reduced if they face difficulties to do an e-transaction